Karakter Jujur Sebagai Aktualisasi Nilai Pancasila - Oksi Peniel Devendrus Mnune; Yakobus Adi Saingo (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The purpose of this research is to discuss honest character as an actualization of Pancasila values. The method used is literature research which is based on scientifically written literature to find a concept that can be studied, analyzed and explained scientifically with data collection activities carried out by reviewing scientific literature such as journals, books, scientific proceedings whose discussions have relevance to the topic that is the focus of this research. The data that has been collected from various literature is then analyzed using a descriptive approach which explains the results that Pancasila, as the ideological pillar of the Indonesian State, has a very important role in forming an honest character in individuals. Honest character is the actualization of Pancasila values, therefore it must be taught and instilled from an early age for each of the nation's future generations. The formation of disciplined character through Pancasila education must be implemented consistently in every lesson at school to help guide the younger generation to increasingly understand the importance of honesty and its consequences in the existence of the Indonesian nation. Pancasila values ??are one of the important foundations in forming an honest character and a society with integrity so that the progress of the nation as a civilized society in accordance with norms can be realized according to the expectations of the Indonesian people.